Variation in soil properties and its influence on the dynamic change of soil erosion resistance to overland flow in the water-level fluctuation zone of the Three Gorges Reservoir, China - Xiao, Hai; Guo, Ping; Zhang, Qianheng; Hu, Huan; Hong, Huan; Zhang, Lun; Yang, Yueshu; Xia, Zhenyao; Li, Mingyi; Kang, Hongliang; Zhang, Guanhua (Catena (Giessen), 2022)
•Dynamic change of soil erosion resistance were quantified.•Soil erosion resistance showed more spatial variation than temporal variation.•Mean weight diameter was the optimal index to describe the soil erodibility.•The critical shear stress was only affected by clay content.•Data strongly support an important effect of plant life-period on soil resistance. The water level fluctuations, rainstorms, and plants could lead to the variation in soil properties in the water-level fluctuation zone (WLFZ) and thus may influence the soil erosion resistance (soil erodibility, Kr, and critical shear stress, τc). However, variation in soil properties and its influence on the dynamic change of soil erosion resistance to overland flow in the WLFZ of the Three Gorges Reservoir (TGR) still unclear and need to be further quantified. Therefore, soil samples from different elevations were collected along a slope profile at different times in the WLFZ of the TGR, then the soil properties and plant biomass were measured and the soil detachment capacity (Dc) were estimated by conducting a scouring experiment. Then the Kr and τc were obtained according to the linear relationship between Dc and shear stress. The results indicated that most measured soil properties suffered low variability but organic matter content showed the moderate variability. Kr varied from 0.10 to 0.17 s m−1 and τc varied in the range of 1.56–2.24 Pa for all sampling points, and both showed spatial and temporal variations. Kr decreased with increasing elevation until reaching a minimum value and then increased spatially, while it showed a decreasing trend or a decreasing trend followed by an increasing trend over time for different elevation segments temporally. τc increased with increasing elevation spatially and increased or showed an increase followed by a decrease over time for different elevation segments temporally. Kr was significantly influenced by clay, silt, and sand content, mean weight diameter and soil organic matter content, while τc was only affected by clay content. These research results highlight the dynamic change of soil erosion resistance and are helpful for understanding the spatial and temporal variations in soil erosion resistance in the WLFZ of the TGR area.